Prevalence and antibiotic resistance of escherichia coli in yong tau foo from night market in Ampang, Selangor / Noor Fazlia Izatie Nor Hashidan - Nor Hashidan, Noor Fazlia Izatie (2018)
Escherichia coli (E. coli) is one of the well - known causative microorganism that caused foodborne diseases like food poisoning. Many transmission agents such as poultry had been known to transmit diseases to human primarily through diet (food) consumption. This study was conducted to isolate and detect the prevalence of Escherichia coli in yong tau foo and to determine the antimicrobial resistance of Escherichia coli isolates from the samples. Samples of raw and boiled yong tau foo (kuey tiaw and sausage) were sampled at night market in Ampang, Selangor. Bacteria were screened by using Eosin Methylene Blue Agar and confirmed by morphological testing and biochemical test. Overall, 10 positive Escherichia coli isolates were analyzed with antibiotic susceptibility tests (AST) by Kirby – Bauer Disc Diffusion method. The resistance of Vancomycin was observed at 100% followed by Tetracycline (80%) and Gentamycin (70%). The resistance towards Levofloxacin (20%) was found to be considerably lower. None of the Escherichia coli were resistant towards Imipenem. The multiple antibiotic resistance indices of Escherichia coli detected in the study ranged from 0.20 to 0.60. The presence of Escherichia coli in yong tau foo revealed that there is a high probability of cross contamination to occur due to inadequate hygiene conditions performed by the food handlers.